La unidad de pago por capitación: 17 años en el Sistema General de Seguridad Social en Salud (2012)
ABSTRACT: To analyze the evolution of the Capitation Payment (UPC for its Spanish name “unidad de pago por capitación”) as well as the methodologies and variables for defining it that have existed in the Colombian Social Security System in Health since its implementation between 1995 and 2011. Methodology: An observational, longitudinal descriptive study. The reference population was made up of all the papers reviewed, including books, journal articles, databases, and official presentations containing the key concepts. Results: It was found that the Capitation Payment (UPC) is valued as an essential element to maintain the financial balance of the health system. From 1995 to 2011 there were a number of methodologies for defining this payment. They ranged from a definition based only on the financial balance and the availability of resources, to a technical study using statistical tools to annually adjust the value of the UPC. Conclusions: The origin of the UPC can be attributed to the system’s orientation toward a market scheme and to the convergence of three basic theories. The variations in the value of the UPC have always resulted in a similar value year after year; this is why even if the methodology for defining it changed, the proportions will be the same when compared to previous years.